Management of Perineal Wounds Following Pelvic Surgery - Mori, George A.; Tiernan, Jim P. (Clinics in Colon and Rectal Surgery, 2022)
Despite advancements in understanding and technique, there remain significant challenges in the management of a complex perineal wound following pelvic surgery. Complications including wound sepsis, fistulation, persistent sinus, and herniation produce additional morbidity and health care costs. This article details the methods of optimizing patient and operative factors to mitigate this risk, alongside strategies to deal with sequelae of wound failure.
Keywords: perineal wound; abdominoperineal tesection; exenteration; vertical rectus abdominis myocutaneous; IGAP; gluteal flap